Electroanalysis and determination of acetaldehyde in fuel ethanol using the reaction with 2,4-dinitrophenylhydrazine - Rodgher, V. S.; Okumura, L. L.; Saczk, A. A.; Stradiotto, Nelson Ramos [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Springer, 2006)
The voltammetric reduction of acetaldehyde was studied in 0.1 M LiOH: LiCl (60: 40 v/v). Welldefined waves can be seen at -1.77 and -1.60 V with the use of hanging mercury and glassy carbon electrodes. Acetaldehyde was shown to react at room temperature with the 2,4-dinitrophenylhydrazine and the product exhibited a differential pulse voltammetric peak at -0.90V, which was well separated from the peaks of the derivative. This allowed the indirect determination of acetaldehyde in the presence of 0.1 M ethanol/tetrabutylammonium perchlorate after 10 min of reaction. Calibration graphs were obtained for 1.00 x 10(-6)-1.00 x 10(-4) M of acetaldehyde. The detection limit is 8.14 x 10(-7) M. The method has been applied satisfactorily to the determination of total aldehyde in fuel ethanol samples without any pretreatment.